Politik Hukum Pidana dalam Perlindungan Korban Kejahatan Ekonomi di Bidang Perbankan - Muhammad Arief Amrullah (Fakultas Hukum Universitas Islam Indonesia, 2002)
As we have seen that corporation te Criminal Code is not the matter of criminal law, so corporation certainly is unreliable criminally. Furthermore if bank Is made for crimepurposeso the direction will be a white color. Under this condition, it means that there no economical victims normatively on banking. The following would be elaborated the problem above from the political perspective of criminal law.